Mendelian randomization to explore the direct or mediating associations between socioeconomic status and lung cancer - Wu, Hong; Yang, Jing; Wang, Hui; Li, Lei (Frontiers in Oncology, 2023)
Objective: The purpose of this study was to verify whether there are direct or mediated causal associations between socioeconomic status and lung cancer. Methods: Pooled statistics were obtained from corresponding genome-wide association studies. The inverse-variance weighted, weighted median, MR‒Egger, MR-PRESSO and contamination-mixture methods were used as supplements to Mendelian randomization (MR) statistical analysis. Cochrane's Q value and the MR‒Egger intercept were used for sensitivity analysis. Results: In the univariate MR analysis, household income and education had protective effects on overall lung cancer (income: P = 5.46×10-4; education: P = 4.79×10-7) and squamous cell lung cancer (income: P = 2.67×10-3; education: P = 1.42×10-10). Smoking and BMI had adverse effects on overall lung cancer (smoking: P = 2.10×10-7; BMI: P = 5.67×10-4) and squamous cell lung cancer (smoking: P = 5.02×10-6; BMI: P = 2.03×10-7). Multivariate MR analysis found that smoking and education were independent risk factors for overall lung cancer (smoking: P = 1.96×10-7; education: P = 3.11×10-3), while smoking was an independent risk factor for squamous cell lung cancer (P = 2.35×10-6). Smoking, education, and household income mediate the effect of BMI on overall lung cancer (smoking 50.0%, education 49.2%, income 25.3%) and squamous cell lung cancer (smoking 34.8%, education 30.8%, income 21.2%). Smoking, education, and BMI mediate the effect of income on overall lung cancer (smoking 13.9%, education 54.8%, BMI 9.4%) and squamous cell lung cancer (smoking 12.6%, education 63.3%, BMI 11.6%). Smoking, BMI, and income mediate the effect of education on squamous cell lung cancer (smoking 24.0%, BMI 6.2%, income 19.4%). Conclusion: Income, education, BMI, and smoking are causally associated with both overall lung cancer and squamous cell lung cancer. Smoking and education are independent association factors for overall lung cancer, while smoking is an independent association factor for squamous cell lung cancer. Smoking and education also play important mediating roles in overall lung cancer and squamous cell lung cancer. No causal relationship was found between multiple risk factors associated with socioeconomic status and lung adenocarcinoma.